Insights into climate variability of the meteorological records from a background monitoring station: the Giordan lighthouse, Gozo [version 2; peer review: 1 approved, 3 approved with reservations] - Martin Saliba; Ryan Vella; Alfred Micallef; Raymond Ellul; Aaron Micallef; Erika Coppola; David Mifsud; James Ciarlo` (Open Research Europe)
Background The Maltese islands are subject to substantial climate variability, with implications for ecosystems and human activities. This study leverages a 26-year dataset from the Giordan Lighthouse Background Monitoring Station (GL) on the island of Gozo to analyse short-term climate variability and its alignment with broader regional tendencies. Methods Hourly meteorological data collected from 1997 to 2022, including wind speed, wind direction, air temperature, relative humidity, and air pressure, were analysed. The study examined diurnal and annual cycles, probability distribution functions, and climate indices to characterise local climate dynamics. Qualitative comparisons were made to existing findings based in Malta to corroborate the results. Results The analysis revealed pronounced seasonal variability in all parameters. Rising air temperatures were detected, consistent with regional warming tendencies. Humidity and wind conditions showed seasonal shifts aligning with observations from other regional monitoring stations. The high-resolution dataset also captured fine-scale temporal patterns, reinforcing the critical value of localised, long-term meteorological monitoring for understanding climatic shifts. Conclusions This study underscores the value of long-term meteorological datasets in detecting climate variability, including a clear warming pattern and seasonal shifts in temperature, humidity, and wind conditions. Continuous monitoring and improved data reliability are essential for enhancing climate assessments and supporting effective adaptation strategies in the Maltese Islands.